(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the issue of financing educational organizations in Russia and foreign countries. The article considers government spending on education as a percentage of GDP, as well as the ratio of state and non-state sources of education financing. Based on the results obtained, a conclusion is formulated about the global role of public finance for the development of education.